DIGITAL COGNITIVE-BEHAVIORAL THERAPY FOR INSOMNIA: SAFETY, LIMITATIONS, AND PATIENT-SPECIFIC CONTRAINDICATIONS - Zofia Hałabuda,; Kornelia Rynkiewicz, (International Journal of Innovative Technologies in Social Science, 2026)
Introduction & objective: Insomnia is a well-established clinical problem that places a burden on the healthcare system. Due to low accessibility to professional therapists, high costs, and geographical barriers, cognitive-behavioural therapy, which is a first-line treatment for insomnia, is rarely prescribed in clinical practice. The development of digital CBT-I was aimed at overcoming those issues. However, there is still limited data regarding the safety and implementation of dCBT-I in real-life settings. Our aim was to select a specific patient group in which the traditional approach to CBT-I is preferred/advised.Review methods: This review is based on a non-systematic review of PubMed articles published between 2015 and 2026.Brief description of state knowledge: In numerous studies, dCBT-I has been proven to be an effective alternative to face-to-face therapy. It can be delivered in several technological forms and may vary in the level of therapist oversight. Although each form of digital CBT-I is to some extent automated, fully automated platforms raise the greatest concerns regarding safety and patient outcomes. Thus, some research suggests that there are patients for whom face-to-face therapy would be advisable.Summary: Digital CBT‑I with therapist oversight may be particularly important for patients with psychiatric disorders, epilepsy, obstructive sleep apnea, safety‑critical occupations, and older adults; however, limited real‑world safety data highlight the need for further research to better define high‑risk groups and refine clinical guidelines.